The effect of metabolic syndrome on controlled ovarian stimulation outcome in infertile women with polycystic ovary syndrome undergoing assisted reproductive technology cycles - Ashraf Moini; Tawoos Rezaee; Ashraf Aleyasin; Arezoo Arabipoor; Marzieh Eslami Moayed (Archives of Endocrinology and Metabolism, 2022)
ABSTRACT Objective: To evaluate the effect of metabolic syndrome (MetS) diagnosis on oocyte quality and pregnancy outcomes in infertile women with polycystic ovary syndrome (PCOS) who undergoing antagonist-controlled ovarian stimulation (COS) and in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Subject and methods: This prospective cohort study was conducted from November 2019 to November 2020 across two university-affiliated infertility centers in Iran. The PCOS diagnosis was defined according to the Rotterdam criteria. The patients prior to IVF/ICSI cycles were evaluated for MetS diagnosis. MetS was detected according to the National Cholesterol Education Program/Adult Treatment Panel III with the presence of at least three or more of the specific clinical criteria. The cycle outcomes were compared between MetS and non-MetS groups. Results: Overall, 68 eligible infertile PCOS patients with MetS diagnosis and 126 without MetS participated. The MetS diagnosis was associated with the increased requirement of gonadotropins and the COS duration significantly (P = 0.001). Although the total numbers of retrieved and MII oocytes, obtained and top-quality embryos as well as clinical pregnancy and live birth rates in the MetS group were lower than those of in the non-MetS group, the differences were not statistically significant (P > 0.05). In follow-up of the obstetrics complications, the rate of preeclampsia was significantly higher in patients with MetS (P = 0.02). Conclusion: MetS diagnosis in PCOS patients was associated with non-significant poor COS and pregnancy outcome. Further studies with larger sample sizes are recommended to clarify the risk of MetS in patients undergoing ART cycles.